Philosophical perspectives on the "War on Terrorism" - Presbey, Gail M. (Value Inquiry Book Series, 2007)
This book responds to the Bush Administration position on the "war on terror." It examines preemption within the context of "just war"; justification for the United States-led invasion of Iraq, with some authors charging that its tactics serve to increase terror; global terrorism; and concepts such as reconciliation, Islamic identity, nationalism, and intervention.